Analytical Thinking Skills that Included in the Content of Math Curriculum : an Analytical Study of Books for First and Second Grades of the Basic Education in the Syrian Arab Republic (Journal of Hama University, 2024)
This research aimed to Identify the availability of the following analytical thinking skills: (Identifying Attributes or Features, Identifying Properties, Observing, Approximation the Similar and the Different, Comparing / Contrast, Grouping/ Tab, Classifying, Establishing Criteria, Ordering and Setting Priorities and Making Sequences, Identifying Relationship, Predicting/ Anticipation, Identifying Cause and Effect, Measuring) in the content of the Math books for the first and second grades. To achieve this goal, the tow researchers adopted the descriptive approach, and they built a list of the analytical thinking skills based on Sternberg’s classification; in its final form, it consisted of (13) skills and (38) indicators to these skills. The content analysis method was used, and the research tool was a content analysis card, that was designed on a list of analytical thinking skills, in order to analyze the research sample; consisting of Math books for first and second grades of the basic education. And the two researchers checked the validity and reliability of the analysis. The results showed that the Math books for first and second grades included all analytical thinking skills, except for the skill of Identifying Cause and Effect. And the most frequent skill was the skill of Measuring. Some of these skills were received in unconsidered proportions, where the focus was on some skills at the expense of others. Also, the gradient in the percentage of including most of the analytical thinking skills between the content of the books for first and second grades was not observed. Consequently, the tow researchers proposed some recommendations.
Keywords: Analytical Thinking Skills; Content of Math Curriculum; The Basic Education